Simulation Model as a Tool for Regional Resilience Assessment - Svoboda, Ondřej; Ibl, Martin; Břízková, Markéta (International Business Information Management Association-IBIMA, 2018)
Disturbances caused by anthropogenic, naturogenic or mixed threats have been, are and will always be the aim of interest to many experts. The region's response to these changes differs from region to region. Regional development is logically linked to economic resilience that is nowadays researched in a number of studies. Regions differ in their ability to adapt to changes stemming from different sources. Less resilient regions are experiencing degradation of the desirable path of regional development, while resilient regions successfully face the challenges. The aim of this paper is to illustrate basic aspects of regional resilience with respect to the law of adaptation and the law of requisite variety, as well as to show the application of transition modelling rules to simulation of regional processes. The next purpose of the paper is to provide a new insight into the link between the concepts of variability, adaptability and resilience.
Simulační model jako nástroj pro hodnocení regionální odolnosti
Keywords: Resilience; Law of Requisite Variety; Law of Adaptation; Agent-Based modelling; Odolnost; Zákon požadované rozmanitosti; Zákon o přizpůsobení; Multiagentní modelování